1994
DOI: 10.1002/cne.903450207
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of individual normal and regenerating optic fibers in the brain of living adult goldfish

Abstract: Retinal arbors in the tectum of living adult goldfish were imaged to determine whether the structural remodelling and refinement that occurs during development continues in adulthood. Individual optic fibers were labelled by making small injections of the lipophilic fluorescent dye DiI into ventral retina and viewing the exposed tectum through a fluorescence microscope equipped with a cooled CCD camera. Arbors were imaged in the living fish every 30-60 minutes for up to 7 hours. Normal adult goldfish showed no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
13
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 50 publications
8
13
0
Order By: Relevance
“…A fish at 70 days of regeneration is shown in Figure 8. This confirms our two previous in vivo imaging studies showing that regenerating optic fibers were typically branched by about 6 weeks after nerve crush (Danks et al, 1994;Johnson et al, 1999).…”
Section: Retinotopic Optic Fibers From Ventral Retinasupporting
confidence: 90%
See 2 more Smart Citations
“…A fish at 70 days of regeneration is shown in Figure 8. This confirms our two previous in vivo imaging studies showing that regenerating optic fibers were typically branched by about 6 weeks after nerve crush (Danks et al, 1994;Johnson et al, 1999).…”
Section: Retinotopic Optic Fibers From Ventral Retinasupporting
confidence: 90%
“…The arrowhead in the panels of Figure 1 indicates a portion of the arbor where varicosities could be seen moving during the imaging period. In agreement with our previous study (Danks et al, 1994), normal arbors were found to be structurally stable, showing no detectable growth or retraction.…”
Section: Normal Arborssupporting
confidence: 90%
See 1 more Smart Citation
“…DiI and related carbocyanine dyes are well tolerated by cells, and fluorescent-labeled cells have normal physiological properties including synaptic transmission (Honig and Hume, 1986). These dyes have previously been microinjetted in organic solvents to achieve discrete labeling of living nonmammalian neurons in situ (Liu and Westerfield, 1990;O'Rourke and Fraser, 1990;Danks et al, 1994), but such organic solvents, in our experience, cause unsatisfactory pathological changes in mammalian neurons. Using the present methods, we have previously established that individual dendritic spines persist and can be recognized over periods of hours (Hosokawa et al, 1992), a condition necessary if modulation of the strength of particular synapses serves as a basis for preservation of memories.…”
Section: Discussionmentioning
confidence: 92%
“…Deflected fibers, however, remained nearly as dispersed as in early regeneration. The methodology for labeling and imaging optic axons in the adult goldfish and the corresponding technical issues has been discussed previously (7,8,20).…”
Section: Resultsmentioning
confidence: 99%